MiR-277/4989 regulate transcriptional landscape during juvenile to adult transition in the parasitic helminth Schistosoma mansoni - Protasio, Anna V.; van Dongen, Stijn; Collins, Julie; Quintais, Leonor; Ribeiro, Diogo M.; Sessler, Florian; Hunt, Martin; Rinaldi, Gabriel; Collins, James J.; Enright, Anton J.; Berriman, Matthew (PLOS Neglected Tropical Diseases, 2017)
Author summary Schistosomes are parasitic helminths that infect a range of different animals causing great morbidity and some level of mortality among endemic populations in sub-Saharan Africa, southeast Asia and regions of south America. RNA has long been known as a translator of the message between DNA and protein. However, it is nowadays well accepted that RNA roles go beyond that of a translator. Such RNA molecules do not translate DNA into protein and are therefore referred to as non-coding RNAs. Here we study a particular type of RNA molecules called microRNA (miRNA). These small RNA molecules are ~ 19–22 nucleotides (nt) in length and their most characterised function so far is that of regulating the bioavailability of messenger RNA for the production of protein. We call this effect post-transcriptional regulation. Previously, it has been shown that different stages of the Schistosoma parasites express different types of miRNAs. Our work focuses in utilising differences in gene expression as the readout of potential post-transcriptional regulation. Using bioinformatics tools we found that members of one miRNA family called miR-277/4989 might be responsible for the change in gene expression observed between juvenile and adult worms. Furthermore, the effect of this miRNA seems to be more prominent in the sexually matured females rather than in the immature “virgin” females.